Hands that Rocked Vivekananda : The Life of his Parents - Bandyopadhyay, Chirasree, (Brill | Manohar Publishers & Distributors, 2021)
Swami Vivekananda has remained an eternal source of inspiration for many. It is, however, not widely known that his inspiration was profoundly influenced by his parents, especially his mother Bhubaneswari Devi. This book essentially covers the period when Bengal Renaissance was at its crest. It gives us a picture of the socio-cultural life of Bengal. This book also covers the life of his parents, who had a profound and lasting impact on his personality, and from whom he inherited his rare and striking qualities. While Biswanath Datta traversed large parts of the country, following the call of his legal profession, Bhubaneswari Devi remained at home, educating her children. The former was erudite, liberal and forthright in his outlook. Likewise, she was a lady of great personality and spiritual attainments. All these traits were passed on to Vivekananda. Though it is a joint biography, the principal emphasis is laid on Vivekananda's mother. Her influence on Vivekananda's life is much more than that of his father. She outlived Vivekananda, while his father died when he was in his youth. Vivekananda's father never lived to see the transformation of his loving son from Narendranath to Vivekananda, but his mother did, and she influenced him till his last days. The entrenched love of Vivekananda for his mother is also recounted, who, despite being sanyasi, never hesitated to do anything for her, even accompanying her to the court for litigation.